Strategy to Increase Merit System Index Value in The Management of State Civil Apparatus in Witness and Victim Protection Agency - Riyadi, Roery Ayu Mayangsari; Silitonga, Mala Sondang; Asropi, Asropi (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
This study was conducted to find factors that influence the Merit System Index Value in State Civil Apparatus Management at the Witness and Victim Protection Agency (LPSK), and to find strategies to increase the Merit System Index Value in State Civil Apparatus Management at the Witness and Victim Protection Agency. The research methodology used is descriptive qualitative. Data were obtained from in-depth interviews with key informants, books, journals, laws and regulations, and other related documents. The results of the study are that the factors that influence the Merit System Index Value in State Civil Apparatus Management at the Witness and Victim Protection Agency include laws and regulations, leadership, diversity, digital transformation, organizational culture, and politics. Therefore, the strategies that need to be carried out by the Witness and Victim Protection Agency to be able to increase the Merit System Index Value in State Civil Apparatus Management include 1) short-term strategies include aspects of socialization and training, determination of policies and regulations, appointment of a Merit System Index improvement work team, development of the Personnel Information System; 2) medium-term strategies include aspects of Merit System evaluation, Talent Management, transparency and accountability, and awards; and 3) long-term strategies include aspects of bureaucratic cultural transformation, career development programs, collaboration, and sustainable innovation.